Effects of regional enamel and prism orientations on bovine enamel bond strength and cohesive strength. (25th June 2018) - Wang, Chaoyang; Ou, Yangyan; Zhang, Ling; Zhou, Zihuai; Li, Mingxing; Xu, Jingqiu; Fan, Jiayan; Fu, Baiping; Hannig, Matthias
Abstract : This study investigated the regional microtensile bond strength (MTBS) and cohesive strength of bovine enamel. The crowns of bovine incisors were sectioned, either horizontally along incisal and cervical thirds to produce horizontal and tangential segments, or longitudinally along the midline to produce longitudinal segments. Half of the horizontal and longitudinal segments were prepared using a 45° bevel. Then, the differently sectioned enamel surfaces were treated with one‐ or two‐step self‐etch adhesives (Clearfil SE Bond or Clearfil S3 Bond) and a composite resin (Clearfil Majesty) was placed. Resin‐bonded enamel samples were cut into beams for use in the MTBS tests. Labial horizontal and longitudinal segments of pure enamel beams were prepared for cohesive strength tests. Enamel microstructures were analyzed by scanning electron microscopy. Three‐wayanova followed by Tukey's post‐hoc HSD multiple comparisons procedure showed that a 45° bevel cut did not statistically significantly improve enamel MTBS, which varied with the different regions. The longitudinally sectioned resin‐bonded enamel samples had the lowest MTBS, and the horizontal enamel cohesive strength was weaker than that of the longitudinal enamel. The scanning electron microscopy fractographs indicated that rows of parallel prisms were detached from the fractured surfaces. In conclusion, the regional enamel MTBS and the cohesive strength are strongly related to the enamel microstructures and prism orientations.